Pengawasan Nazir dalam Pengelolaan Tanah Wakaf Masjid di Kabupaten Sidrap: Perbandingan Mazhab Syafi‘i dan Undang-Undang Wakaf - Alfina S; Ahmad, Nur; Verawati (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The management of mosque waqf land requires an effective monitoring system to ensure the sustainability of its social and religious functions; however, in practice at the local level, the monitoring mechanism for nazirs often faces structural and normative problems. This study aims to analyze the patterns of supervision of nazir in the management of the Nur Hasyim Mosque waqf land in Bulucenrana Village, Pitu Riawa District, Sidenreng Rappang Regency through a comparative approach between the Shafi'i school of thought and the provisions of Law Number 41 of 2004 concerning Waqf and its implementing regulations. The research focuses on the form of supervision, factors hindering supervision, and the conformity of supervisory practices with the normative framework of fiqh and positive law. This study uses a qualitative method with field research, integrating a juridical-normative and sociological approach to bridge the analysis of legal texts and empirical realities. Data was obtained through observation, in-depth interviews with nazirs, wakifs, and related parties, as well as documentation, then analyzed descriptively and analytically through the stages of reduction, presentation, and conclusion drawing. The results of the study show that supervision of nazirs is carried out through efforts to manage, develop, and implement waqf, but it has not been optimal. The main obstacles to supervision include the lack of guidance from the Indonesian Waqf Board (BWI) and the lack of certification of mosque waqf land. From the perspective of the Shafi'i school of thought, the authority of supervision should ideally lie with judges or the government, while in the practice of this study, supervision is actually carried out by the waqf, so it is not fully in line with the views of the school of thought. According to Law Number 41 of 2004 in conjunction with Government Regulation Number 42 of 2006, the supervision of waqf is carried out by the government and the community, both actively and passively. These findings indicate normative compatibility between the Shafi'i school of thought and positive law, but there are discrepancies at the implementation level.